PENGARUH KECERDASAN VISULA SPASIAL DAN SELF CONCEPT TERHADAP KEMAMPUAN BERPIKIR KREATIF - Rahmawati, Sri Desi; Mulyatna, Fauzi; Gusniwati, Mira (Program Studi Pendidikan Matematika FIP UNHASY, 2022)
This study aims to determine the effect of visual-spatial intelligence and self-concept on creative thinking skills. This research was conducted at Yapermas Junior High School and Taman Siswa Junior High School with a sample of 46 students in class VIII for the 2021/2022 academic year. The research method used is a correlational survey method. The instruments used are description tests (visual spatial intelligence and creative thinking skills) and questionnaires (self concept), all instruments have been validated. Before testing the hypothesis, the data requirements were tested, including: normality test with chi square test, all data were normally distributed, linearity test obtained all data with a linear pattern, and multicollinearity test obtained all data between variables X1 and X2, there was no multicollinearity. Then the hypothesis test is carried out to get the equation persamaan Y=12,58 +0,22 X1+0,75X2 and with a level of 5% it is obtained Fcount (6,99) > Ftable (3,21 ) then H0 is rejected. The results of the study concluded that 1) there was an effect of spatial visual intelligence and self-concept on the ability to think creatively, 2) there was an effect of visual-spatial intelligence on the ability to think creatively, and 3) there was an influence of self-concept on the ability to think creatively.